CURCUMIN INCREASES THE SENSITIVITY OF BREAST CANCER CELLS TO TAMOXIFEN BY INHIBITING MRP2 MRNA EXPRESSION OF EFFLUX TRANSPORTER MRP2 - KRISNAMURTI, DESAK GEDE BUDI; WANANDI, SEPTELIA INAWATI; LOUISA, MELVA (International Journal of Applied Pharmaceutics, 2019)
Objective: Tamoxifen is the drug of choice to treat breast cancer positive for estrogen receptor. Long-term use of tamoxifen can induce multidrug resistance (MDR) associated with decreased sensitivity of cancer cells to the drug. One of the causes of MDR is overexpression of efflux transporter multidrug resistance-associated protein (MRP)2. Various drugs are known to act as MRP2 inhibitors, including curcumin. This study investigated the effects of curcumin on the sensitivity of breast cancer cells to tamoxifen through inhibition of MRP2. Methods: We used MCF-7 cells that were previously exposed to long-term tamoxifen treatment [MCF-7(T) cells]. MCF-7(T) cells were treated with 1 µM tamoxifen, curcumin (5, 10, and 20 µM), combinations of curcumin (5, 10, and 20 µM) and 1 µM tamoxifen, or 10 µM nevirapine (a known MRP2 inhibitor) for 5 d. Then, the cells were harvested, counted to assess cell viability, and evaluated for MRP2 mRNA expression. Results: Treatment with curcumin alone or in combination with tamoxifen significantly reduced cell viability at all curcumin concentrations compared with the control. The reduction in cell viability was accompanied by a reduced level of MRP2 mRNA expression. Conclusion: Application of curcumin to MCF-7 cells previously exposed to long-term tamoxifen treatment increase the sensitivity of cancer cells to tamoxifen. The increased sensitivity of these cells was attributed, at least in part, to inhibition of the efflux transporter MRP2.